An Innovative Approach for Understanding the Patterns in Distribution and Extraction of Non-Timber Forest Products in Chitwan Annapurna Landscape, Nepal - Silwal, Ramesh; Maharjan, Sajana; Shrestha, Bhaskar; Chitale, Vishwas; Murthy, Manchiraju (Indian Forester, 2018)
Non-timber forest products (NTFPs) form more than 5% of national GDP of Nepal and are facing threat due to over extraction. We demonstrate a novel approach of identifying prospective zones of distribution of NTFPs by integrating satellite data, vegetation data, and published literature. Present study provides comprehensive analysis on distribution and utilization patterns of 109 economically and ecologically important NTFPs from central Nepal. Highest distribution of NTFPs is in sub-tropical zone, followed by temperate, and sub-alpine zone. The approach is replicable and could be crucial in understanding patterns of distribution, extraction, and revenue of NTFPs for better conservation and management.